2022
DOI: 10.3390/universe8100493
|View full text |Cite
|
Sign up to set email alerts
|

Gap Transients Interacting with Circumstellar Medium

Abstract: In the last 20 years, modern wide-field surveys discovered a new class of peculiar transients, which lie in the luminosity gap between standard supernovae and classical novae. These transients are often called “intermediate luminosity optical transients” or “gap transients”. They are usually distinguished in subgroups based on their phenomenology, such as supernova impostors, intermediate luminosity red transients, and luminous red novae. In this review, we present a brief overview of their observational featu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 171 publications
0
6
0
Order By: Relevance
“…About five orders of magnitude separate the peak luminosity of the faintest Galactic objects such as OGLE 2002-BLG-360 (Tylenda et al 2013) and V1309 Sco (Mason et al 2010;Tylenda et al 2011) from bright extragalactic events (0 M V −15 mag; see, e.g., the sample presented by Pastorello et al 2019a). The latter objects, with Tables A1-A3 are only available at the CDS via anonymous ftp to cdsarc.cds.unistra.fr (130.79.128.5) or via https:// cdsarc.cds.unistra.fr/viz-bin/cat/J/A+A/671/A158 intermediate luminosity between those of classical novae and core-collapse supernovae, are 'gap transients' (Kasliwal 2012;Cai et al 2022a). LRNe have structured light curves, with a phase of slowly rising luminosity lasting months to years, followed by a major outburst.…”
Section: Introductionmentioning
confidence: 99%
“…About five orders of magnitude separate the peak luminosity of the faintest Galactic objects such as OGLE 2002-BLG-360 (Tylenda et al 2013) and V1309 Sco (Mason et al 2010;Tylenda et al 2011) from bright extragalactic events (0 M V −15 mag; see, e.g., the sample presented by Pastorello et al 2019a). The latter objects, with Tables A1-A3 are only available at the CDS via anonymous ftp to cdsarc.cds.unistra.fr (130.79.128.5) or via https:// cdsarc.cds.unistra.fr/viz-bin/cat/J/A+A/671/A158 intermediate luminosity between those of classical novae and core-collapse supernovae, are 'gap transients' (Kasliwal 2012;Cai et al 2022a). LRNe have structured light curves, with a phase of slowly rising luminosity lasting months to years, followed by a major outburst.…”
Section: Introductionmentioning
confidence: 99%
“…ILOTs (or gap transients) form a heterogeneous group with diverse time scales, luminosities, and shapes of lightcurves (a partial list of papers include, e.g., Banerjee et al [5], Blagorodnova et al [6], Boian, & Groh [7], Bond et al [8], Cai et al [9,10,11], Jencson et al [4], Kami ński et al [12], Karambelkar et al [13], Kasliwal [14,15], Mason et al [16], Mould et al [17], Ofek et al [18], Pastorello et al [19][20][21][22], Rau et al [23], Stritzinger et al [24], Tylenda et al [25][26][27], and Wadhwa et al [28]).…”
Section: Adopt the Theoretical Definition Of Intermediate Luminosity ...mentioning
confidence: 99%
“…Since the discovery of V1309 Sco (Tylenda et al 2011), a luminous red nova (LRN) and a confirmed binary merger, many more new LRNe have been discovered (Kurtenkov et al 2015;Blagorodnova et al 2017Blagorodnova et al ,2021Cai et al 2019Cai et al , 2022aCai et al , 2022bPastorello et al 2019Pastorello et al , 2021aPastorello et al , 2021b, to name a few. It is argued that, at least for some of the LRNe, the progenitors are binary stars that have undergone common envelope evolution (CEE; Ivanova et al 2013a), one of the most mysterious events in binary evolution.…”
Section: Introductionmentioning
confidence: 99%